Konteks Sistem Sekunder Di Situs Cabean Kunti, Boyolali (Pandangan Masyarakat dan Dampaknya pada Kelestarian Situs) - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 2005)
The secondary system context is the BCB (heritage) that applies in today's society's life system. This phenomenon becomes interesting because the